Life-Saving Extracorporeal Membrane Oxygenation Combined with Hemoperfusion for a Pregnant Woman with COVID-19 Severe Acute Respiratory Distress Syndrome - Phongphithakchai, Atthaphong; Saipetch, Niwat; Praditau-krit, Suntornwit; Boonsrirat, Ussanee; Sathaporn, Natthaka; Konwai, Sirihatai (Journal of Health Science and Medical Research, 2025)
The pandemic of the novel coronavirus (COVID-19) affected millions of people worldwide, causing high mortality and morbidity, especially in pregnancy. The management of COVID-19, which progresses to severe acute respiratory distress syndrome during pregnancy, is very challenging. Herein we report a 35-year-old pregnant woman in her second trimester (16 weeks of gestational age) who presented with a productive cough and progressive dyspnea. She was diagnosed with a severe COVID-19 infection, confirmed by PCR testing. During hospitalization, she developed severe acute respiratory distress syndrome (ARDS) and was referred to a tertiary hospital. Despite the use of antiviral therapy, steroids, mechanical ventilators, and muscle relaxants, she still had significant hypoxemia. Thus, she underwent veno-venous extracorporeal membrane oxygenation (VV-ECMO). Due to the limitations of immunomodulatory therapy in pregnancy, our team decided to perform extracorporeal cytokine removal therapy with HA330 adsorbent hemoperfusion to remove circulatory cytokines and proinflammatory mediators and suppress the hyperinflammatory response. After 3 consecutive days of hemoperfusion, her C-reactive protein and interleukin-6 were controlled. On the 13th day of ICU admission, her clinical conditions, including pulmonary function, were improving, and she was successfully weaned off the VV-ECMO. A chest X-ray showed she was completely free of ARDs. The patient left the hospital with good clinical status and a viable fetus. We conclude that pregnant women infected with COVID-19 who develop refractory hypoxemia with cytokine storm syndrome may benefit from combined VV-ECMO and hemoperfusion as a rescue therapy.